Respuestas
Respuesta dada por:
2
Respuesta:
3b-2a
Explicación paso a paso:
AB = AD - BD
AB = a - b
Luego nos dicen que
BC = 2AB
BC = 2(a - b)
Podríamos encontrar CD como
CD = AD - AB - BC
CD = a - (a - b) - 2(a - b)
CD = a - a + b - 2a +2b
CD = 3b - 2a
Respuesta dada por:
3
Respuesta:
CD = 3b - 2a
Explicación paso a paso:
Adjuntos:
![](https://es-static.z-dn.net/files/d2b/b902b4f675aecb326c0b167cc4511bbd.jpg)
![](https://es-static.z-dn.net/files/d07/cb20b5b8906207b98c1c5fe4e79be28e.jpg)
kenowashi:
Tienes instagram?
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años